A Comparison of Pitching Biomechanics and Sport Specialization in High School Pitchers - Tyler J. Hamer; Adam B. Rosen; Samuel J. Wilkins; Kristen F. Nicholson; Garrett S. Bullock; Brian A. Knarr (International Journal of Sports Physical Therapy)
# Background